EFEKTIVITAS MINYAK ATSIRI KULIT JERUK BERGAMOT (Citrus bergamia) DALAM MASKER GEL PEEL-OFF SEBAGAI ANTI BAKTERI Staphylococcus aureus ATCC 29213 - Intan Martha Cahyani; Retno Artiyani (Jurnal Ilmiah Manuntung, 2017)
Staphylococcus aureus is a bacterial strain that causes acne. Linalool and limoneneis are the ingredients of Citrus bergamia essensial oil which has antibacterial activity Staphylococcus aureus. This research aimed to examine the effective consentration of Citrus bergamiaessensial oil as antibacterial Staphylococcus aureus ATCC 29213. Citrus bergamia essensial oil is made in series a concentration of 1%, 2% and 3% for testing of antibacterial activity using the pitting diffusion method. Based on the test results of antibacterial activity gained an average diameter of inhibitory zone Citrus bergamiaessensial oil in a row 1,151 cm; 1,529 cm; 1,683 cm. The statistically test results showed significant difference in the antibacterial activity of Citrus bergamiaessensial oil in concentrations 1%, 2% and 3% to the growth of Staphylococcus aureus ATCC 29213. Citrus bergamiaessensial oil has effective concentration 3% as stapgylocuccus aureus antibacterial and made peel-off gel mask formula. Test of antibacterial activity obtained resistibility zone diameter 1,259 cm. The result of t-test indicated that the Citrus bergamiaessensial oil peel-off gel mask has significant affect on antibacterial activity of Citrus bergamiaessensial oil.